Phosphoarginine stimulation of Na(+)-Ca2+ exchange in squid axons--a new pathway for metabolic regulation? - DiPolo, R (1995)
1. [Na+]o-dependent Ca2+ efflux (forward Na(+)-Ca2+ exchange), [32P]ATP wash-out curves and [ATP] were measured in internally dialysed squid giant axons at 17-18 degrees C. 2. We found that dialysing squid axons without ATP and with [Ca2+]i around 1 microM the basal levels of the [Na+]o-dependent Ca2+ efflux were significantly higher in the presence of N omega-phosphoarginine (PA). Phosphocreatine, a related phosphagen, is without effect. 3. PA stimulation of the Na(+)-Ca2+ exchange occurs in the complete absence of ATP (< 1 microM), being independent of, and additive to, the ATP-stimulated [Na+]o-dependent Ca2+ efflux. PA stimulation of [Na+]o-dependent Ca2+ efflux is fully and rapidly reversible with a Km around 7.7 mM. Activation by saturating [PA] is equivalent in magnitude to that of ATP. 4. PA stimulation of Na(+)-Ca2+ exchange is markedly dependent on intracellular Ca2+ and Mg2+ ions. Below 0.5 microM Ca2+i PA effect is negligible, becoming noticeable between 0.8 and 2 microM. In addition, Ca2+i considerably increases the rate at which PA activates the Na(+)-Ca2+ exchange. Although there is no absolute requirement of the PA effect for Mg2+ ions, this divalent cation largely stimulates the PA effect. 5. This work demonstrates, for the first time, the presence in squid axons of a new form of metabolic regulation of the Na(+)-Ca2+ exchange directly and solely related to PA and different from that of MgATP. This novel mechanism is likely to play a physiological role in Ca2+ extrusion through the Na(+)-Ca2+ exchanger, particularly at micromolar [Ca2+]i.